2014
DOI: 10.1007/s12237-014-9848-8
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Deposition and Accretion Rates in Tidal Marshes Are Highly Variable Along Estuarine Salinity and Flooding Gradients

Abstract: Vertical accretion in estuarine marshes depends on rates of sediment deposition and is a complex function of different interacting variables. In times of climate change and associated sea-level rise, knowledge about the relation between these variables and sediment deposition and accretion rates is gaining high importance. Therefore, we studied spatial and temporal variation in short-term sediment deposition rates and its possible predictors in three marsh types along an estuarine salinity gradient. Between Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 51 publications
5
49
1
2
Order By: Relevance
“…In fact, the ability of salt marshes to cope with SLR and their future sustainability depends on many dynamic and interacting processes influencing the potential for wetland submergence (e.g. vertical accretion, ability to migrate inland)7444849. Therefore, in addition to the expected SLR, other variables must be considered when assessing salt marsh vulnerability and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the ability of salt marshes to cope with SLR and their future sustainability depends on many dynamic and interacting processes influencing the potential for wetland submergence (e.g. vertical accretion, ability to migrate inland)7444849. Therefore, in addition to the expected SLR, other variables must be considered when assessing salt marsh vulnerability and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…See Table 1 Hydrobiologia vary greatly within sites and that the majority of sediment accretion data available are generalised from few samples. However, whilst extrapolation of accretion data from few samples can be problematic due to the spatial variability of sediment deposition (Butzeck et al, 2015), the exclusion of these data is likely to provide greater model prediction errors. Results from this study have shown that sediment accretion rates taking into account increased storminess are of a similar magnitude to isostatic uplift (1.6-2.5 mm/year compared with 2.0-2.8 mm/year respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Surface-elevation change and, consequently, also succession in estuarine marshes are influenced by various factors such as sediment deposition, above-and below-ground production, compaction, and erosion (Bricker-Urso et al 1989;Neubauer et al 2002;Nolte et al 2013;Butzeck et al 2015). Furthermore, rates of sea-level rise (Wahl et al 2011) and isostatic effects of the last ice age (Vink et al 2007) that have resulted in deep subsidence play an important role in the fate of estuarine marshes.…”
Section: Introductionmentioning
confidence: 99%